Analisis Butir Soal Dynamic Assessment untuk Mengukur Pemahaman Konsep Klasifikasi Tumbuhan pada Mahasiswa - Tutik Wulandari; Murni Ramli*; Muzzazinah Muzzazinah (Universitas Syiah Kuala, 2022)
Based on the study of literature and documents, the material analysis of plant classification is considered difficult. The assessments that have been used on plant classification materials have not been equipped with feedback. This study aims to determine the validity, reliability, level of difficulty, discriminatory power, detection of bias and unidimensionality of dynamic assessment instruments on plant classification materials. Development research method with the ADDIE model. The research sample was 121 biology education students who were selected by purposive random sampling. The results showed the validity of the questions in the form of 12 fit questions with the Rasch modeling having an MNSQ infit of 0.80-1.22. The reliability of the items in the 0.97 category is very good and the respondent's reliability is 0.31 in the weak category. While the level of difficulty of the questions is unknown, there are four categories, namely 3 very easy questions, 4 easy questions, 2 difficult questions, and 3 very difficult questions. The discriminatory power of questions with a separation index of 6.71 and an index of separation of questions of 0.67. Detection bias shows that gender does not discriminate against item items and unidimensionality of item items with 36.5% raw variance with sufficient category. The dynamic assessment instrument is suitable to be used to measure the understanding of the concept of plant classification in students